Answer:
Explanation:
Heat capacity A = 3 x heat capacity of B
initial temperature of A = 2 x initial temperature of B
TA = 2 TB
Let T be the final temperature of the system
Heat lost by A is equal to the heat gained by B
mass of A x specific heat of A x (TA - T) = mass of B x specific heat of B x ( T - TB)
heat capacity of A x ( TA - T) = heat capacity of B x ( T - TB)
3 x heat capacity of B x ( TA - T) = heat capacity of B x ( T - TB)
3 TA - 3 T = T - TB
6 TB + TB = 4 T
T = 1.75 TB
The answer should be speed hope this helps
Sunglasses to shield from the sun
B is the answer you need and i honestly got this question on a middle school test
you must be in different area then me